Sistem Informasi Geografis Pengenalan Pariwisata Kabupaten Pacitan Berbasis Web - Santoso, Agung Nugroho Dwi, Fatah Yasin Al Irsyadi, S.T., M.T (2016)
Pacitan has many tourist attractions, so far the information about the objects travel (tourism map) in any tourist locations that provided by the government is incomplete. Tourism map can make tourist easier to visit tourist attractions without having to ask the local people. Nowadays, almost every tourist spots in Pacitan districts do not have travel maps, so the information of the tourist attractions sites that should be a tourist destination for tourists is not socialized. This will be affected to the income of the local government. Researchers designed this geographic information system introduction Pacitan tourism as a media for promotion tourist spots in Pacitan and also as media directions to the spot of tourist attractions. Observations is that made in Pacitan by collecting data on tourist information contained in Pacitan. The results obtained from this researches is a web of geographic information system introduction Pacitan tourism that contains information of photos, videos, descriptions, facilities, prices, and coordinates of the tourist sites in Pacitan. In the manufacture of web geographic information system, researchers tested black box method, and the black box method testing of the system does not have bugs.